(untitled) (MAUSAM, 1969)
Infrared radiative heat flux and instantaneous rate of temperature change have been computed for Indian, subcontinent for monsoon season by making use of the numerical method developed for the purpose. The effects of water Vapour alone have been considered. It is found that the radiative beat loss near the surface is minimum over the Western Ghats. Over northeast and northwest India, the radiative heat loss is relatively high. Also, the radiative cooling integrated from the surface upto 300 mb indicates a large cooling over northeast and northwest India (>loC per day) and relatively small cooling over the southern Peninsula ( <0.25°C per day). Analysis of the day to day values of net flux and temperature suggest no cause-and-effect relationship. However, a good correspondence has been noticed between net flux, temperature and total moisture content as far as surface level is concerned. The day to day values of net flux at higher levels follow very closely to those at the surface.